(untitled) (Revista de Estudos da Linguagem, 2006)
This work will investigate the more and more frequently observedphenomenon of boundary transgressions that one can find inthe world of non-literary and literary texts in forms that utilizetypological intertextuality. There will be a discussion of the playwith patterns, the norms and conventions in the area of textualgenres, especially, by means of montage, the mixture and breachingof textual patterns that are employed in a contrastive sensecompared to the normal use, in order to attract the attention ofan audience that is exposed to an abundance of texts and inorder to seduce the receptor into reading the particular text underdiscussion. Forms and types will be shown, as well as abundanceand variety of those breaches of the “canon”. Finally, what happensto the signs in that ambivalence between canon and dissolutionof canon during the process of reception will be shown; that is, aspecific kind of semiose will be observed – namely, a semiose ofalienation that is bound to those non-conventional texts.